2013
DOI: 10.1016/j.virol.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibodies are unable to inhibit direct viral cell-to-cell spread of human cytomegalovirus

Abstract: Infection with human cytomegalovirus (CMV) during pregnancy is the most common cause of congenital disorders, and can lead to severe life-long disabilities with associated high cost of care. Since there is no vaccine or effective treatment, current efforts are focused on identifying potent neutralizing antibodies. A panel of CMV monoclonal antibodies identified from patent applications, was synthesized and expressed in order to reproduce data from the literature showing that anti-glycoprotein B antibodies neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…This finding further stresses the complexity of the fusion process based on stoichiometry, as well as geometry, of complex formation. In addition, a recent paper using a plaque reduction assay format concluded that LJP539 (previously designated 4I22) was unable to inhibit cell-to-cell spread at an antibody concentration of 10ϫ EC 50 (26). In our studies, we observed a 76-fold shift in the EC 50 of LJP539 between the neutralization and syncytium formation assays, demonstrating that significantly larger amounts of antibody are needed to inhibit cellcell spread.…”
Section: Discussionsupporting
confidence: 45%
“…This finding further stresses the complexity of the fusion process based on stoichiometry, as well as geometry, of complex formation. In addition, a recent paper using a plaque reduction assay format concluded that LJP539 (previously designated 4I22) was unable to inhibit cell-to-cell spread at an antibody concentration of 10ϫ EC 50 (26). In our studies, we observed a 76-fold shift in the EC 50 of LJP539 between the neutralization and syncytium formation assays, demonstrating that significantly larger amounts of antibody are needed to inhibit cellcell spread.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, although RG7667 inhibits CMV entry into epithelial cells, endothelial cells, macrophages, and fibroblasts (21) and would also likely inhibit entry into dendritic cells (37), the formal possibility exists that RG7667 does not neutralize entry into an unidentified cell type. RG7667 may also not inhibit CMV cell-to-cell spread, which may contribute to CMV viremia (38). Even though we observed robust neutralization in vitro using two antibodies, we might have demonstrated greater activity if RG7667 had included a greater number of monoclonal antibodies directed at different targets.…”
Section: Discussionmentioning
confidence: 74%
“…There are reports suggesting that cell-associated HCMV spread may be totally independent of virion glycoproteins or dependent on glycoproteins different from those promoting cell-free HCMV spread [40,41]. This was supported by findings that cell-associated spread in cell culture cannot be inhibited by neutralizing antibodies directed against virion proteins know to be involved in cell-free virus spread [47]. Similarly, by using recombinant PDGFR-α-Fc, we could not reduce spread of wt TB40 or TB40-UL131Astop viruses to a level below the level achieved by methylcellulose overlays known to block spread of supernatant virus.…”
Section: Discussionmentioning
confidence: 94%